2020
DOI: 10.1038/s41401-020-0474-7
|View full text |Cite
|
Sign up to set email alerts
|

WNK-SPAK/OSR1-NCC kinase signaling pathway as a novel target for the treatment of salt-sensitive hypertension

Abstract: Hypertension is the most prevalent health condition worldwide, affecting ~1 billion people. Gordon's syndrome is a form of secondary hypertension that can arise due to a number of possible mutations in key genes that encode proteins in a pathway containing the With No Lysine [K] (WNK) and its downstream target kinases, SPS/Ste20-related proline-alanine-rich kinase (SPAK) and oxidative stress responsive kinase 1 (OSR1). This pathway regulates the activity of the thiazide-sensitive sodium chloride cotransporter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 85 publications
0
17
0
Order By: Relevance
“…WNKs play a key role in maintaining ion homeostasis, and their dysregulation can lead to diseases such as hypertension [ 135 ]. In recent years, more and more studies have found that WNKs are overexpressed or downregulated in cancer tissues, contributing to tumor growth, metastasis and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…WNKs play a key role in maintaining ion homeostasis, and their dysregulation can lead to diseases such as hypertension [ 135 ]. In recent years, more and more studies have found that WNKs are overexpressed or downregulated in cancer tissues, contributing to tumor growth, metastasis and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant renal SGK1/WNK-SPAK/OSR1 regulation is involved in disease conditions such as Gordon’s Syndrome and Gitelman-like conditions [ 7 , 8 , 9 , 10 ]. Upstream kinases of the WNK-SPAK/OSR1 axis, such as SGK1 (Serum/Glucocorticoid Regulated Kinase 1) and protein kinase B (also known as AKT), both phosphorylate WNK kinases and therefore stimulate SPAK/OSR1 to activate renal ion channels including: NKCC2, NCC, ENaC, and ROMK [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the inhibition/stimulation of KCC2/NKCC1 pair via protein phosphorylation is through a regulatory mechanism that works in a reciprocal pattern [53,64] and members of the with-no-lysine kinase (WNKs) family as well as their downstream targets; STE20/SPS1-related proline/alanine rich kinase (SPAK) and oxidative stress response kinase (OSR1) are the most prominent kinases that regulate this process [52,[64][65][66][67]. Consequently, impaired ion homeostasis resulting from mutation in the physiological function of some of this transporter pair and/or their upstream regulators may be detrimental and subsequently result in diminished inhibition and augmented network hyperexcitability, which underlies numerous neurological disorders [52,66,[68][69][70][71] including HD [58][59][60].…”
Section: Introductionmentioning
confidence: 99%
“…When [Cl − ] i exceeds equilibrium, depolarisation events contribute to the onset of neurological disease [35,46]. Decreased KCC2 expression coupled with increased NKCC1 expression and/or activity has been documented in several pathologies [63,68,69,71], including HD [58][59][60]. In HD, HTT is mutated (mHTT) and acts to alter KCC2 and NKCC1 expressions and activity [58,59] through mechanisms that remain undetermined.…”
Section: Introductionmentioning
confidence: 99%